The Addition of Opuntia ficus-indica Ethanolic Extract to a Skimmed Milk-Based Extender Impacts Ram Sperm Quality - Larbi Allai; Xavier Druart; Pinar Terzioğlu; Noureddine Louanjli; Boubker Nasser; Mehmet Ozturk; Bouchra El Amiri (Veterinary Medicine International)
Recently, researchers have focused on the use of natural antioxidants to improve semen quality as a key element for successful artificial insemination. In this context, the first aim of this study was to determine the antioxidant activity and composition (minerals, vitamins, and sugars) of Opuntia ficus-indica cladode ethanolic extract (ETHEX). A further purpose of the study was to investigate the effect of ETHEX supplementation on the quality of liquid ram semen extended with skim milk (SM) at 5°C. The antioxidant activity of ETHEX was studied using free radical 1, 1-diphenyl-2-picrylhydrazyl (DPPH•) assay. The mineral composition and the sugar and vitamin contents of ETHEX were determined using an inductively coupled plasma optical emission spectrometry (ICP-OES) and HPLC-DAD-RID analytical instruments. As a second part, semen was collected from five Boujaâd rams with an artificial vagina. The ejaculates with more than 70% motility were pooled, extended with skim milk (SM) extender without (control) or supplemented with 1–8% of ETHEX (37°C; 0.8 × 109 sperm/mL). Sperm quality parameters were assessed at 8, 24, 48, and 72 h. The results showed that ETHEX had a higher antioxidant activity compared to those of ascorbic acid and butylated hydroxytoluene (BHT). Furthermore, ETHEX contains a considerable amount of minerals, vitamins, and sugars. The inclusion of 1 or 2% ETHEX in SM increased the sperm motility, viability, and membrane integrity and decreased the abnormality of spontaneous and catalyzed lipids peroxidation (p<0.05) up to 72 h. In addition, semen diluted with 1 and 2% ETHEX decreased the level of DNA fragmentation compared to the control group (p<0.05). In conclusion, the ETHEX could be recommended to improve the quality of liquid ram spermatozoa. However, its effects on artificial insemination should be further studied.